How Effective is the Self-Reliance Agenda in Uganda’s Refugee Response? - Ahaibwe, Gemma; Depio, Sheila (Economic Policy Research Centre, 2019)
The 2006 Uganda’s Refugee Act has been widely commended for being progressive and exemplary. Some of the distinctive provisions of the law include allocation of arable land to refugee households, access to public social services and the freedom to seek employment and operate businesses. These generous provisions were expected to empower refugees to sustain themselves overtime. The recent surge in refugee arrivals and the increasing protracted nature of refugee situations, coupled with undependable and inadequate refugee assistance, sustainable solutions like promotion of self-reliance among refugees become imperative. This policy brief highlights the extent of self-reliance among refugees, identifies factors promoting or hindering self-reliance among refugees and proposes policy options. The brief is based on the 2017 EPRC refugee survey that was conducted in the rural settlements of Nakivale, Rwamwanja, Bidibidi, Rhino camp, Pagirinya and urban refugees in Kampala (Kisenyi, Katwe and Nsyambya).